Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus - Kikuchi, Namiki; Konishi, Kazuhiko (Zootaxa, 2018)
We discovered Dentilabus Heinrich (Icneumoninae: Platylabini) for the first time from the Eastern Palearctic region. Two new species, D. nigripodus sp. n. [Japan and Korea] and D. iyoensis sp. n. [Japan] are described. Dentilabus nigripodus resembles its Western Palearctic congener, D. variegatus (Wesmael), but they can be easily distinguished by the uniformly black hind femora in D. nigripodus. With the inclusion of D. iyoensis, we also redefine the generic limits of Dentilabus. A key to Palearctic species of the genus is provided.